(untitled) (Practitioner Research, 2023)
The study investigated the impact of employee satisfaction on the performance of selected Microfinance banks in Nigeria, focusing on five banks located in Osun State. The specific objectives included exploring the relationship between employee satisfaction and the performance of these Microfinance banks, as well as identifying the factors—prompt salary, job security, and fringe benefits—that affect employee satisfaction in Nigerian microfinance institutions. A purposive sampling technique was employed to select 40 employees, and data were collected using well-structured questionnaires. The analysis involved descriptive statistics and regression analysis. The findings of the study indicated a positive relationship between employee satisfaction and the performance of Microfinance banks. Furthermore, the results highlighted that factor such as prompt payment of salary, job security, and the provision of fringe benefits significantly and positively influenced employee satisfaction within the selected microfinance banks in Osun state.In light of these results, the study recommends that microfinance banks should take proactive measures to enhance employee satisfaction, particularly in the areas of prompt salary payments, job security, and the provision of fringe benefits. Strengthening these aspects of employee engagement is suggested as a means to improve overall performance in the microfinance sector. By prioritizing the well-being and satisfaction of their workforce, microfinance banks can foster a positive work environment conducive to increased efficiency and effectiveness.